Pengaruh Service Convenience, Service Sophistication, Dan Brand Experience Terhadap Kepercayaan Pelanggan Dan Kesediaan Untuk Membayar Harga Premium Pada Layanan Premium Streaming Musik: Studi Pada Pelanggan Layanan Premium Streaming Musik Di Kota Semarang - Muhammad Arya Nurrafi; Susilo Toto Raharjo (Faculty of Economics and Business Diponegoro University, 2025)
Currently there is a phenomenon where the behavior and reasons for internet users in Indonesia who use the internet to listen to music do not make music streaming service customers willing to pay premium prices. Based on previous research, it was found that several factors can influence customer trust in premium music streaming services, which can lead to a willingness to pay premium prices for premium music streaming services, namely service convenience, service sophistication, and brand experience. This study aims to test and analyze the influence of service convenience, service sophistication, and brand experience on consumer willingness to pay premium prices for premium music streaming services with trust as a mediator.Sampling was done using purposive sampling technique, the total sample used was 134 respondents who were users of premium music streaming services in the city of Semarang who had subscribed by paying premium prices for premium music streaming services. The data analysis technique used in this study was using SEM (Structural Equation Model) analysis with the SmartPLS program, and the data collection technique used a questionnaire.The results showed that service convenience, service sophistication, and brand experience had a positive effect on customer trust in premium music streaming services. Service convenience, service sophistication, and brand experience did not have a significant effect on the willingness to pay premium prices for premium music streaming services. Customer trust in premium music streaming services has a positive effect on the willingness to pay premium prices for premium music streaming services.